Effects of MTNR1B Genetic Variants on Individual Susceptibility to Gestational Diabetes Mellitus: A Meta-Analysis - Jia, Guangliang; Gao, Yanxiang; Li, Chunzhi; Zhang, Yanqin (American Journal of Perinatology, 2020)
Objective Whether melatonin receptor 1B (MTNR1B) variants are implicated in gestational diabetes mellitus (GDM) remains unclear. Therefore, we performed this meta-analysis to obtain a more conclusive result on associations between MTNR1B variants and GDM.Study Design Literature research was performed in PubMed, Web of Science, Embase, and China National Knowledge Infrastructure. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated.Results A total of 17 studies were eligible for analyses. Pooled overall analyses showed that rs1387153 (dominant model: p = 0.0002, OR = 0.78, 95% CI: 0.68–0.89; recessive model: p < 0.0001, OR = 1.46, 95% CI: 1.24–1.73; allele model: p < 0.0001, OR = 0.78, 95% CI: 0.72–0.84), rs4753426 (recessive model: p = 0.01, OR = 1.75, 95% CI: 1.14–2.68; allele model: p = 0.01, OR = 0.69, 95% CI: 0.51–0.93), and rs10830963 (dominant model: p < 0.0001, OR = 0.72, 95% CI: 0.65–0.78; recessive model: p < 0.0001, OR = 1.56, 95% CI: 1.40–1.74; allele model: p < 0.0001, OR = 0.73, 95% CI: 0.69–0.78) variants were all significantly associated with the susceptibility to GDM. Further subgroup analyses by ethnicity of participants yielded similar positive results.Conclusion Our findings indicated that MTNR1B rs1387153, rs4753426, and rs10830963 variants might serve as genetic biomarkers of GDM.
Keywords: melatonin receptor 1B; genetic variants; gestational diabetes mellitus; meta-analysis